Obstáculos e potencialidades no uso das tecnologias de informação e comunicação como prática dialógica na educação - Cunha, Andreza Lima Marimon da (2013)
This study intend to analyze the communication between teachers and students through information and communication technologies. The information and communication technologies are increasingly gaining importance as teaching resources of the school, but we question: how these technologies act as mediators of communication? The technologies can make easier the teacher-pupil dialogue, which we know is not easy and natural. In this context of obstacles and difficulties, we checked how teachers and students are ready for this new challenge of education which is to understand and use the potential offered by ICTs in the school environment and beyond applying them critically. With this discussion, motivated by the author's experience as a journalist in an educational institution, the research tries to advance the new field that is born of the intersection between pedagogy and information technologies and communication, linking theory concepts of communication, education, educommunication, pedagogy of communication and studies on the cyberspace. To investigate the difficulties and opportunities of using technology to mediate communication between teachers and students, we use data from the survey ICT Education 2011, published by the Brazilian Internet Steering Committee (CGI.br) in Brazil in 2012. For the analysis, we try to provide a profile and trends of students and teachers in the use of computers and the internet and affinity with new technologies, establish relationships of Internet use by students and teachers with other variables, such as region, public or private system, income, and compare habits and activities of students and teachers on the internet, as well as skills and training. We observed, then, widespread presence of information technology and communication in school and daily life of students and teachers as well as the recognition of teachers about the importance of application of ICTs in school. What it appears is that ICT is still little used in school with the purpose of communication and are seen as tools for storage and transmission of information, without constituting any change in educational paradigm. We propose, in this context, a critical view of ICTs, based on collaborative and communicative aspects, covering its use as a dialogical practice for the collective construction of knowledge, referring us to the pedagogy of Freire.